A new genus and species of Sciomyzidae (Diptera) from the Neotropical Region - Marinoni, Luciane; Zumbado, Manuel A.; Knutson, Lloyd (Zootaxa, 2004)
A new genus, Neuzina, is described from specimens collected in Brazil (Par ), Venezuela (Guarico) and Costa Rica (Guanacaste). The species Neuzina diminuta is described as the type species of the genus and based on the presence of the proepisternal seta and characters of male and female genitalia the genus is placed in the subfamily Sciomyzinae, tribe Sciomyzini.